Mineralogical characterization of gold in the Aurora ore zone in the Björkdal gold mine, northern Sweden – implications for metal recovery - Åström, Krister (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2022)
The Aurora zone is an ore zone which was recently discovered in the Björkdal gold mine, northern Sweden, and it has been the main focus of mining and exploration activities for the past few years (Pressacco et al., 2020). The purpose of this project is to determine how gold occurs in the Aurora zone. A three-day long campaign was therefore done at the processing plant at the Björkdal mine where 11 000 tonnes of ore from the drive Aurora 370/1650 E+W were processed. The issue regarding the ore from the Aurora zone is that it has a lower recovery compared to the rest of the mine. Six chip samples, 12 samples from the ingoing plant feed and two tailing samples were analyzed using optical microscopy, scanning electron microscopy (SEM), and automated mineralogy (QEMSCAN). This was done to determine the mineralogy, grain size distribution, mineral associations, textures and modal mineralogy which all are factors that could influence the metal recovery at the processing plant. The samples were prepared using the cold mounting method and epoxy mounts were created. After cutting, grinding, and polishing, the sections were ready to be examined. Optical microscopy was performed using a Nikon ECLIPSE E600 POL microscope. Ten epoxy mounts were carbon coated and automated mineralogy was performed on nine of them in a ZEISS Sigma 300 VP using a recipe (analysis mode) for “bright phase search”. Manual point-ID analysis was done using a ZEISS MERLIN SEM. Fifty gold grains were identified in this study, 48 of them in the chip samples and two of them in the ingoing-feed samples. 64% of them were associated with silicates, 22% were quartz associated, 12% were associated with bismuth minerals and 2% of them were associated with sulfides. The grain size distribution has a range between 0.7 and 19 μm and the median grain size is 4.8 μm. The gold grains identified from the Aurora zone have a significantly smaller median grain size than gold from other parts of the mine. The majority of the gold grains identified in this study, have a ...